Co-designing resources to support the transition from child to adult health services for young people with cerebral palsy: A design thinking approach - Fortune, Jennifer; Burke, Jessica; Dillon, Conor; Dillon, Sally; O’Toole, Sharon; Enright, Ann; Flynn, Annmarie; Manikandan, Manjula; Kroll, Thilo; Lavelle, Grace; Ryan, Jennifer M. (Frontiers in Rehabilitation Sciences, 2022)
Introduction Design thinking is a human-centred process that aims to identify the needs of end-users and iteratively develop solutions. Involving end-users in the development and design of solutions may enhance effectiveness by increasing focus on the needs of the target population. This paper describes the process of co-designing resources to support the transition from child-centred to adult-orientated health services using a design thinking approach. Methods Five co-design workshops were conducted remotely with a young person advisory group and parent advisory group. A design thinking process guided by the Stanford D.School approach was used to understand the transition needs of young people and their parents and iteratively develop solutions to improve end-user experience. Results Eight resource prototypes were generated: 1) designated transition coordinator, 2) digital stories of transition experience 3) written informational support 4) transition website, 5) transition checklists and worksheets 6) transition App, 7) transition programme or course and 8) educational programme for health professionals. Conclusion Design thinking is a feasible approach to identify, characterise and prioritise resources collaboratively with end-user partners.